Primary HPV testing versus cytology-based cervical screening in women in Australia vaccinated for HPV and unvaccinated: effectiveness and economic assessment for the National Cervical Screening Program - Jie-Bin Lew, MPH; Kate T Simms, PhD; Megan A Smith, MPH; Michaela Hall, BAdvSc; Yoon-Jung Kang, PhD; Xiang Ming Xu, MPH; Michael Caruana, DPhil; Louiza Sofia Velentzis, PhD; Tracey Bessell, PhD; Marion Saville, MBChB; Prof Ian Hammond, MBBS; Prof Karen Canfell, DPhil (The Lancet Public Health, 2017)
Background: Australia's National Cervical Screening Program currently recommends cytological screening every 2 years for women aged 18–69 years. Human papillomavirus (HPV) vaccination was implemented in 2007 with high population coverage, and falls in high-grade lesions in young women have been reported extensively. This decline prompted a major review of the National Cervical Screening Program and new clinical management guidelines, for which we undertook this analysis. Methods: We did effectiveness modelling and an economic assessment of potential new screening strategies, using a model of HPV transmission, vaccination, natural history, and cervical screening. First, we evaluated 132 screening strategies, including those based on cytology and primary HPV testing. Second, after a recommendation was made to adopt primary HPV screening with partial genotyping and direct referral to colposcopy of women positive for HPV16/18, we evaluated the final effect of HPV screening after incorporating new clinical guidelines for women positive for HPV. Both evaluations considered both unvaccinated and vaccinated cohorts. Findings: Strategies entailing HPV testing every 5 years and either partial genotyping for HPV16/18 or cytological co-testing were the most effective. One of the most effective and cost-effective strategies comprised primary HPV screening with referral of women positive for oncogenic HPV16/18 direct to colposcopy, with reflex cytological triage for women with other oncogenic types and direct referral for those in this group with high-grade cytological findings. After incorporating detailed clinical guidelines recommendations, this strategy is predicted to reduce cervical cancer incidence and mortality by 31% and 36%, respectively, in unvaccinated cohorts, and by 24% and 29%, respectively, in cohorts offered vaccination. Furthermore, this strategy is predicted to reduce costs by up to 19% for unvaccinated cohorts and 26% for cohorts offered vaccination, compared with the current programme. Interpretation: Primary HPV screening every 5 years with partial genotyping is predicted to be substantially more effective and potentially cost-saving compared with the current cytology-based screening programme undertaken every 2 years. These findings underpin the decision to transition to primary HPV screening with partial genotyping in the Australian National Cervical Screening Program, which will occur in May, 2017. Funding: Department of Health, Australia.